A beamline‐compatible STED microscope for combined visible‐light and X‐ray studies of biological matter. (17th May 2019) - Bernhardt, Marten; Nicolas, Jan-David; Osterhoff, Markus; Mittelstädt, Haugen; Reuss, Matthias; Harke, Benjamin; Wittmeier, Andrew; Sprung, Michael; Köster, Sarah; Salditt, Tim
Abstract : Details of design, construction and implementation of the first in situ STED microscope, which has been installed on the optical table of a synchrotron endstation instrument, are presented. Abstract : A dedicated stimulated emission depletion (STED) microscope had been designed and implemented into the Göttingen Instrument for Nano‐Imaging with X‐rays (GINIX) at the synchrotron beamline P10 of the PETRA III storage ring (DESY, Hamburg). The microscope was installed on the same optical table used for X‐ray holography and scanning small‐angle X‐ray scattering (SAXS). Scanning SAXS was implemented with the Kirkpatrick–Baez (KB) nano‐focusing optics of GINIX, while X‐ray holography used a combined KB and X‐ray waveguide optical system for full‐field projection recordings at a defocus position of the object. The STED optical axis was aligned (anti‐)parallel to the focused synchrotron beam and was laterally displaced from the KB focus. This close proximity between the STED and the X‐ray probe enabled in situ combined recordings on the same biological cell, tissue or any other biomolecular sample, using the same environment and mounting. Here, the instrumentation and experimental details of this correlative microscopy approach are described, as first published in our preceding work [Bernhardt et al. (2018), Nat. Commun. 9, 3641], and the capabilities of correlative STED microscopy, X‐ray holography and scanning SAXS are illustrated by presenting additional datasets on cardiac tissue cells with labeled actin cytoskeleton.